Stress Analysis on T-joint Welded Joint using Manual Calculation and Numerical Analysis - SUKARIA (NIM : 13113093), KEVIN
Currently, method on evaluating stress on welded joints is based on manual calculation which refers to the agreed standard. Problem arises when the complexity of the welded joint application is increased making it harder to analyse by using manual calculation method, one of the solution to this is by using the help of numerical analysis. The problem with numerical analysis is that is it not covered in the agreed standard. This final project will analyse the stress distribution when a welded joints is subjected to a critical force according to AWS D1.1-2015. The critical force value is acquired from manual calculation and then it will act as a force during simulation by using ANSYS Workbench software so that the stress distribution can be acquired. Hopefully from the stress distribution data we can identify the connection between manual calculation method and numerical analysis method. After stress distribution data is acquired by using surface and path method, is it found that when a welded joints is subjected to critical force that will cause 100 MPa stress on the effective area, gives a result of 55 MPa instead when analysed using numerical analysis. By using path and surface fiture, is it also possible to acquire stress concentration factor data on weld root by dividing maximum stress with average stress on weld throat. Stress analysis on T-joint welded joint by numerical analysis can be done and calibrated by using path and surface fiture on ANSYS and is it also found that as the throat of the welded joint gets bigger, so does the stress concentration factor on weld root.